Virulence factors of the Zoonotic Pathogen Vibrio alginolyticus: a review and bibliometric analysis - Sheikh Mohamed, Hassan Ibrahim; Alhamadin, Nawal Ismail Issa; Liew, Hon Jung; Fadhlina, Anis; Abd Wahid, Mohd Effendy; Musa, Najiah; Khan Chowdhury, Ahmed Jalal (2024)
Vibrio alginolyticus is an opportunistic Gram-negative marine bacterium that infects animals and humans. Its virulence is associated with numerous factors such as cytotoxicity, adhesion and biofilm formation. This review aimed to quantitatively assess the V. alginolyticus’s virulence factors to identify the main mechanisms of infection. A systematic literature search was conducted using SCOPUS databases up to 31 December 2022. The bibliometric analysis was performed using VOSviewer software. The results showed that toxins are the most common virulence factor making up more than 50% of virulence-related keywords. This was followed by adhesion/biofilm (12%), antibiotic resistance (9%) and quorum sensing (9%). In terms of cytotoxicity, hemolysins were the most common toxins, while in terms of secretion system, type III secretion system (T3SS) was the most common. Extracellular polysaccharide production was the main parameter related to adhesion and biofilm. In terms of antibiotic resistance, extended-spectrum β-lactamases (ESBLs) genes were the most common, and for quorum sensing, N-acyl homoserine lactone (AHL) was the most common. Vibrio pathogenicity island was also identified as a mechanism for accumulating virulence factors. Toxin-coregulated pilus (Tcp) was identified as the main motility-related virulence factor. This review reports that quorum sensing and kinase inhibitors are promising drug targets. Identifying these mechanisms can help in establishing ideal drug targets and management approaches for V. alginolyticus-related infections.